MECHANICAL DURABILITY OF 3D PRINTED FACIAL PROSTHESES COMPARED TO TRADITIONAL SILICONE POLYMER PROSTHESES - Zardawi, Faraedon M.; Wildgoose, David G; van Noort, Richard; Yates, Julian M. (European Scientific Journal, ESJ, 2015)
Purpose: To test the effect of natural and accelerated weathering conditions on the mechanical properties of 3D printed starch samples infiltrated with a maxillofacial silicone polymer. Materials and Methods: A total of 72 samples (dumbbell-shaped, trouserlegs samples, and hardness blocks) were manufactured from silicone polymer (SP) and starch printed and infiltrated silicone polymer (SPIS) according to industry standards (ASTM). Thus, they were set out to evaluate the key mechanical properties of the SPIS (tensile strength, tear strength, percentage elongation, and hardness test). Specimens were exposed to different natural weathering (outdoor, ambient, and dark environment for 4 months) and artificial weathering conditions (2 weeks exposure and 6 weeks exposure) were compared to those of pure silicone polymer (SP). One way analysis of variance ANOVA was used to test the results statistically. Results: Exposure to 4 month natural weathering conditions recorded a significant difference in tensile strength between the control group and the three test groups for SP samples (p<0.05). However, there was no significant differences between the three test groups (p>0.05).Tear strength statistical analysis showed a significant differences between the control group for the SP samples and the other three test samples (p<0.05). Furthermore, SPIS samples demonstrated a significant increase in tear strength of the indoor samples compared to the control samples and the outdoor samples (p<0.05). However, there was no significant difference (p>0.05) observed between the control values and the two other test groups. However, percentage elongation recorded no significant differences between the control group and the test groups for SP samples, or between the test samples in the same group (p>0.05). Percentage elongation for SPIS recorded non-significant differences (p>0.05) between the control values and the dark samples. However, when compared to the outdoor samples, there was a significant difference (p<0.05) between the control and the indoor samples. Hardness test also recorded significant differences (p<0.05) statistically between the control data and the test data for both SP and SPIS samples. Furthermore, artificial weathering condition was more detrimental and showed significant deterioration of some of the mechanical properties of both SP and SPIS specimens when they were exposed for 2 weeks and 6 weeks. Deterioration was more significant at six weeks exposure than 2 weeks when compared to non weathered control group. Conclusions The general properties of facial prostheses were affected non-significantly by exposure to four months natural weathering for both pure silicone polymer SP and starch printed infiltrated polymers SPIS. However, accelerated weathering conditions were significantly deteriorated for the silicone polymer infiltrated starch models SPIS.